MaqFACS (Macaque Facial Action Coding System) can be used to document facial movements in Barbary macaques (Macaca sylvanus) - Églantine Julle-Danière; Jérôme Micheletta; Jamie Whitehouse; Marine Joly; Carolin Gass; Anne M. Burrows; Bridget M. Waller (PeerJ, 2015)
Human and non-human primates exhibit facial movements or displays to communicate with one another. The evolution of form and function of those displays could be better understood through multispecies comparisons. Anatomically based coding systems (Facial Action Coding Systems: FACS) are developed to enable such comparisons because they are standardized and systematic and aid identification of homologous expressions underpinned by similar muscle contractions. To date, FACS has been developed for humans, and subsequently modified for chimpanzees, rhesus macaques, orangutans, hylobatids, dogs, and cats. Here, we wanted to test whether the MaqFACS system developed in rhesus macaques (Macaca mulatta) could be used to code facial movements in Barbary macaques (M. sylvanus), a species phylogenetically close to the rhesus macaques. The findings show that the facial movement capacity of Barbary macaques can be reliably coded using the MaqFACS. We found differences in use and form of some movements, most likely due to specializations in the communicative repertoire of each species, rather than morphological differences.